2010
DOI: 10.1074/jbc.m110.143685
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Hydrogen Peroxide Induces Oxidation and Activation of AMP-activated Protein Kinase*

Abstract: Although metabolic conditions associated with an increased AMP/ATP ratio are primary factors in the activation of 5-adenosine monophosphate-activated protein kinase (AMPK), a number of recent studies have shown that increased intracellular levels of reactive oxygen species can stimulate AMPK activity, even without a decrease in cellular levels of ATP. We found that exposure of recombinant AMPK␣␤␥ complex or HEK 293 cells to H 2 O 2 was associated with increased kinase activity and also resulted in oxidative mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
300
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 369 publications
(314 citation statements)
references
References 72 publications
10
300
1
3
Order By: Relevance
“…AMPK activation through ROS has been previously demonstrated among others in endothelial cells (36), HepG2 hepatocarcinoma cells (37) and vascular smooth muscle cells (38) which may occur before or without alteration in the ATP/AMP ratio (38)(39)(40). In this respect it has been recently shown that physiologically relevant concentrations of H 2 O 2 can activate AMPK through oxidative modification of the AMPKα subunit, and it was discussed that AMPK activation, in addition to being a response to alterations in intracellular metabolic pathways, is directly influenced by cellular redox status (41). The data of the present study shed new light on the role of AMPK activity on cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK activation through ROS has been previously demonstrated among others in endothelial cells (36), HepG2 hepatocarcinoma cells (37) and vascular smooth muscle cells (38) which may occur before or without alteration in the ATP/AMP ratio (38)(39)(40). In this respect it has been recently shown that physiologically relevant concentrations of H 2 O 2 can activate AMPK through oxidative modification of the AMPKα subunit, and it was discussed that AMPK activation, in addition to being a response to alterations in intracellular metabolic pathways, is directly influenced by cellular redox status (41). The data of the present study shed new light on the role of AMPK activity on cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of mice with 5-aminoimidazole-4-carboxamide-1-β-Dribofuranoside (AICAR) or metformin, two inducers of AMPK activation, reduced the severity of lipopolysaccharide (LPS)-induced acute inflammatory lung injury (11,16). However, there is little evidence that AMPK is activated in inflammatory states, such as acute lung injury, despite the presence of conditions including increased release of reactive oxygen species and diminished generation of ATP, which would be expected to result in AMPK activation (9,(17)(18)(19). Therefore, a potentially important, and presently unanswered question, relates to the mechanisms that may prevent activation of AMPK in such conditions.…”
Section: Toll-like Receptor 4 Engagement Inhibits Adenosine 5′-monophmentioning
confidence: 99%
“…Classically, activation of AMPK has been described to occur under conditions of cellular stress that affect the balance between cellular adenosine 5′-triphosphate (ATP), adenosine 5′-diphosphate (ADP) and AMP and involves direct binding of AMP and ADP to the AMPK γ subunit, which then results in phosphorylation of Thr172 within the AMPK α activating loop (3)(4)(5)(6)(7)(8). Recent studies have shown that exposure of cells to reactive oxygen species or glycogen can induce AMPK activation independently of changes in cellular ATP-to-AMP ratios (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Western Blot analysis was performed as described previously (44,45). Briefly, cell lysates of murine bone marrow neutrophils (3.5 × 10 6 /well) were prepared using lysis buffer containing Tris pH 7.4 (50 mmol/L), NaCl (150 mmol/L), NP-40 (0.5%, vol/vol), EDTA (1 mmol/L), EGTA (1 mmol/L), okadaic acid (1 nmol/L) and protease inhibitors.…”
Section: Western Blot Analysismentioning
confidence: 99%